The Novel Tail-anchored Membrane Protein Mff Controls Mitochondrial and Peroxisomal Fission in Mammalian Cells - Gandre-Babbe, Shilpa (The American Society for Cell Biology, 2008)
Few components of the mitochondrial fission machinery are known, even though mitochondrial fission is a complex process of vital importance for cell growth and survival. Here, we describe a novel protein that controls mitochondrial fission. This protein was identified in a small interfering RNA (siRNA) screen using Drosophila cells. The human homologue of this protein was named Mitochondrial fission factor (Mff). Mitochondria of cells transfected with Mff siRNA form a closed network similar to the mitochondrial networks formed when cells are transfected with siRNA for two established fission proteins, Drp1 and Fis1. Like Drp1 and Fis1 siRNA, Mff siRNA also inhibits fission induced by loss of mitochondrial membrane potential, it delays cytochrome c release from mitochondria and further progression of apoptosis, and it inhibits peroxisomal fission. Mff and Fis1 are both tail anchored in the mitochondrial outer membrane, but other parts of these proteins are very different and they exist in separate 200-kDa complexes, suggesting that they play different roles in the fission process. We conclude that Mff is a novel component of a conserved membrane fission pathway used for constitutive and induced fission of mitochondria and peroxisomes.